Maturity framework for e-Government in Oman - Al-Rawahi, Hamed S. (Cranfield University, 2004)
The aim of this research was to develop a model for successfully managing the development of e-government in Oman. E-government refers to the transaction of government business with citizens by electronic means, including email and the internet. The outcome of a series of workshops for managers involved in IT in Oman was that a number of issues would need to be investigated before starting to implement e- govenment on a large scale, and there was seen to be a need to develop a systematic roadmap. The management of the Y2K project in Oman was then evaluated, and practical lessons were learned which would be applicable to subsequent national-scale IT projects. Ways of measuring the progress of countries regarding e-government, and a number of basic management models for introducing e-government, were found by researching the literature. These models covered fewer management aspects than had been found in this research. One important model was the Maturity Framework, which had been applied with some success for managing IT in one international company and one UK Government agency. It was decided to develop a maturity framework for e-government, incorporating the best ideas from the literature, and adding new ideas from the research carried out so far. Detail was added to the new framework, called the POTIRDMO framework, by research involving a large number of IT stakeholders in Oman. The completed POTIRDMO framework has been tested in use and has been compared against frameworks developed by other Governments. The new framework is more comprehensive than previous frameworks because it includes People and Organisational aspects of management, in addition to Technology aspects. It also defines the Characteristics of each stage, the Tasks to be done, and the Measures of completion. Road mapping and benchmarking functions are implicit within the model. It is now being used to manage the development of e-government in Oman.